2000
DOI: 10.3758/bf03211579
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in metacognition: Evidence against a general metacognitive ability

Abstract: Individual differences in metacognitive accuracy are generally thought to reflect differences in metacognitive ability. If so, memory monitoring performance should be consistent across different metacognitive tasks and show high test-retest reliability. Two experiments examined these possibilities, using four common metacognitive tasks: ease of learning judgments, feeling of knowing judgments, judgments of learning, and text comprehension monitoring. Alternate-forms correlations were computed for metacognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
154
1
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(184 citation statements)
references
References 74 publications
(92 reference statements)
21
154
1
8
Order By: Relevance
“…It may be that successful learners are better at making metacognitive predictions, but the demonstrated link between monitoring accuracy and test performance has been mixed. Several studies have shown a positive correlation between metacognitive ability and test performance (Bisanz, Vesonder, & Voss, 1978;Maki & Berry, 1984;Yan, 1994), whereas others have shown that learning ability is not related to metacognitive accuracy (Kearney & Zechmeister, 1989;Kelemen, Frost, & Weaver, 2000;Lovelace, 1984;Maki & Swett, 1987;Underwood, 1966). The present results support the proposal that lower confidence may change how people evaluate and plan their study, which may play an important role in later test accuracy.…”
Section: General R R Discussionsupporting
confidence: 78%
“…It may be that successful learners are better at making metacognitive predictions, but the demonstrated link between monitoring accuracy and test performance has been mixed. Several studies have shown a positive correlation between metacognitive ability and test performance (Bisanz, Vesonder, & Voss, 1978;Maki & Berry, 1984;Yan, 1994), whereas others have shown that learning ability is not related to metacognitive accuracy (Kearney & Zechmeister, 1989;Kelemen, Frost, & Weaver, 2000;Lovelace, 1984;Maki & Swett, 1987;Underwood, 1966). The present results support the proposal that lower confidence may change how people evaluate and plan their study, which may play an important role in later test accuracy.…”
Section: General R R Discussionsupporting
confidence: 78%
“…Given the interdependence of metacognition and performance discussed above, one explanation for this null result might be methodological in nature, as a performance-confidence relationship is naturally harder to quantify than performance itself. A similar line of thought led Keleman et al to speculate that 'stable metacognitive performance might be detected using very large numbers of trials' [112]. In support of this view, Fleming et al showed good split-half reliability (r ¼ 0.69) in a perceptual decision task with hundreds of trials [21], and metacognitive accuracy has been shown to be stable across two perceptual tasks (r ¼ 0.71), despite performance itself being uncorrelated (r ¼ 0.05; figure 3) [70].…”
Section: Neural Basis Of Metacognitive Accuracy (A) Studies Of Metamementioning
confidence: 90%
“…Judgments of learning involve assessing how well one thinks one has learnt a piece of information, and judgements of confidence involve making retrospective judgments about how certain one is in one's knowledge about a piece of information. The literature on typical development suggests that metamemory accuracy is only modestly correlated across different types of metamemory judgement (Kelemen, et al, 2000;Leonesio & Nelson, 1990). This has led to suggestions that different metamemory judgments may be based on different sources of information.…”
Section: Discussionmentioning
confidence: 99%